A comparative study of bacteriological profile and outcomes in infective exacerbation of chronic obstructive pulmonary disease and bronchial asthma - B S Nagaraja; Arjun P Chandrashekar; Anindita Menon (Wolters Kluwer Medknow Publications, 2023)
Background: According to the Global Burden of Disease 2018, chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide, and in India, COPD is the second leading cause of death among noncommunicable diseases. Among India's 1.31 billion people, about 6% of children and 2% of adults have bronchial asthma. Infective exacerbations of both COPD and Bronchial asthma are common. However, there are some differences in the bacterial spectra between the two conditions, and profiling the bacteria responsible for the exacerbations will help in choosing appropriate antibiotics and also to combat the issue of drug resistance. Aims: (1) To analyze the bacteriological profile of patients with infective exacerbation of COPD and bronchial asthma. (2) To study the outcomes among these patients. Subjects and Methods: The study was a prospective observational study conducted from November 2019 to May 2020 in Bangalore Medical College and Research Institute on 50 patients diagnosed with acute exacerbation of COPD and 50 patients diagnosed with an exacerbation of bronchial asthma. Detailed history, physical examination, and standard laboratory tests were done on admission. Sputum samples were collected from the patients and analyzed by Gram staining and microscopy and also by culture. The differences between the two groups were analyzed. The progression of the disease and the outcomes were observed. Results: 100 patients were included in our study, 50 each in COPD and bronchial asthma. The study was conducted in hospitals attached to BMCRI. Bacteriological profile was assessed by sputum culture and antibiotic sensitivity in the COPD and asthma groups, respectively. In our study, in the COPD group, majority (80%) of patients were males, the mean age was 64.34 ± 9.876, and 80% were smokers with 20% having exposure to biomass. The most common growth in COPD exacerbation was Streptococcus pneumoniae (18%) followed by Haemophilus influenzae and Klebsiella pneumoniae. Mortality in COPD exacerbation was 12%. In the asthma group, female preponderance was seen (54%), mean age was 40.64 ± 13.11. Majority of patients were cases of childhood asthma. Growth was seen in 32% of exacerbations and the most common organism was Streptococcus pneumoniae. Mortality was 4% and importantly due to comorbidities. Conclusions: Bacterial exacerbations are more common in COPD, while it is not so in bronchial asthma. Viral exacerbations and atypical bacterial exacerbations are more common and asthma associated with pneumonia is the cause for culture growth. Mortality is considerably low in the asthma group compared to COPD exacerbations.